Faktor-faktor Yang Mempengaruhi Aktivitas Mengikuti Pengajian Dikalangan Remaja Provinsi Lampung : Study Komparatif Terhadap Aktivitas Kelompok Pengajian Rohani Islam Di Perkotaan Dan Pedesaan - Mubasit, Mubasit; Jasmadi, Jasmadi (Jurusan Bimbingan dan Konseling Islam, 2023)
Da'wah Islam is an invitation to follow a religion that is Rahmatan Lil Alamiin, namely a religion that is present in the midst of society and contains an invitation to do good and forbid evil deeds. At present there is a tendency for recitation activities to be